What we know about teaching writing - Dombey, Henrietta (Preschool and Primary Education, 2013)
The teaching of reading is the subject of much national and international study and the focus of considerable attention from education administrators and politicians, as well as educators. The teaching of writing receives less attention. Yet it is both complex and an essential part of education. This paper presents an overview of research into the teaching of writing in Anglophone countries from the last 40 years or so. Unlike the teaching of reading, there appears to be little controversy over the most effective approaches: researchers in the US, UK, New Zealand and Australia appear to be in broad agreement about the most effective ways of going about this complex task. While those learning to write in English have to struggle with a particularly opaque orthography, the findings from the studies cited below could also apply to teaching in other languages, particularly those with alphabetic orthographies.